PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA BAGIAN SUMBER DAYA ALAM SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - mega ratnawati (ADMINISTRASI PUBLIK, 2018)
The purpose of this study is to determine whether there is influence of motivation on the performance of employees in the Natural Resources Section of the Regional Secretariat of East Kutai Regency. The analytical tool used is a simple linear regression test. Sampling using the method determined, with the number of samples of 45 employees in the Natural Resources Section of the Regional Secretariat of East Kutai Regency, from data obtained through questionnaires. The result of simple regression analysis between motivation variable and employee performance obtained by the equation Y = 1,83 + 0,5127 X. Further correlation value r equal to 0,616. After the result of the analysis compared with r table (critical price table) where N = 45 with significance level of 0.05, it is empirical r count is bigger than r table (0,616> 0,3059). Thus the working hypothesis (hi) accepted the truth and rejected the null hypothesis (ho) This means there is influence between work motivation and employee performance in the Natural Resources Section of the Regional Secretariat of East Kutai Regency.